Petrologia magnética dos Granitoides Neoarqueanos da Suíte Vila Jussara - Província Carajás, Cráton Amazônico. - SOUSA, Luan Alexandre Martins de (Universidade Federal do Pará, 2019)
The Vila Jussara suite (VJs) comprises several granitic stocks of Neoarchean age (~ 2.75-2.73Ga), intrusive in Mesoarchean units and distributed in the central and northern portions of the Sapucaia Domain in Carajás Province. The VJs granitoids consist of reduced and oxidized ferrous granites as well as magnesian granites. Petrographically, four types of rocks were distinguished in the VJs: (1) Biotite-hornblende monzogranite (BHMzG); (2) Biotitehornblende tonalite (BHTnl); (3) biotite monzogranite (BMzG); (4) Hornblende-biotite granodiorite (HBGd). The study of magnetic susceptibility (MS) in VJs rocks showed very variable values (MS, 0.14 x 10-3 to 30.13 x10-3), distributed in three populations (A, B and C). Based on the magnetic behavior and the Fe and Ti oxides, BHMzG was divided into two subgroups: the first with very low to low MS (MS 0.14 x 10-3 and 0.81 x 10-3; populations A and B1 ) marked by the dominance of ilmenite with titanite crowns, as well as the subordinate presence of magnetite and pyrite crystals, the latter evidenced only in subpopulation B1; the second shows moderate to high values of MS (1.91 x10-3 to 6.02 x10-3, subpopulations B3 and C1), being characterized by the dominance of magnetite over ilmenite. The BHTnl presented moderate values of MS (0.85 x10-3 to 1.36 x10-3, subpopulation B2, with the exception of a single sample with high value of MS belonging to subpopulation C2) and present dominance of pyrite, seconded by magnetite which is more abundant than ilmenite. BMzG and HBGd are characterized by relatively higher MS values (MS, respectively, 2.14 x10-3 to 6.01 x10-3 and MS 6.02 x10-3 to 25.0 x10 -3, subpopulations B3, C1 and C2) and both are characterized by the dominance of magnetite over pyrite, with rare occurrences of ilmenite. In geochemical terms, the first subgroup of BHMzG exhibits silica >70% and affinity with the reduced ferrous granites; the second presents silica varying between 63 and 70% and is similar to oxidized ferrous granites. All other groups show magnesium granite characteristics with increasing BHTnl silica for HBGd and BMzG. The biotite compositions vary in the passage of BHMzG from subgroup 1 to subgroup 2 and from these to magnesian granites and are compatible with those from the Ilmenite series for transitional between Ilmenite and Magnetite series and, finally, Magnetite series. In this same sense, amphibole compositions indicate low, moderate and transition between moderate and high oxygen fugacity. The four VJs strains formed in different degrees of oxidation, the first subgroup of BHMzG formed under reduced (<FMQ) or moderately reduced (coincident or slightly above FMQ) conditions; the second group of BHMzG was formed under moderately oxidizing conditions (between NNO and NNO-0.5); finally the magnesian granites formed under oxidizing conditions with comparatively higher fO2 (between NNO and NNO + 1). The magnetite is usually partially martitized and the pyrite is intensely altered to goethite, forming pseudomorphs. In addition to the four described varieties, biotita-hornblenda sienogranites occur to medium equigranular monzogranites that paradoxically exhibit high MS value and high magnetite modal content, along with FeOt/(FeOt+MgO) ratios in extremely high total rock, biotite and amphibole, indicative of training under reducing conditions. It is assumed that these granites formed under such conditions, but it was not possible to explain the high modal contents of magnetite and the high MS. The comparison of the VJs with related Neoarchean granitoids from the Carajás Province reveals that the first subgroup of BHMzG exhibits strong similarity with the granites of the Planalto suite, the Estrela granitic complex and the reduced granites of the granitoids of the Vila União region, while that the other varieties are closer to the oxidized ferroan and magnesian granites of Vila União. The VJs granitoids differ from those of the Matok Neoarchean pluton, of the Limpopo Belt in South Africa, because they are the latter more markedly magnesian and more strongly oxidized.